HUBUNGAN DUKUNGAN SOSIAL TEMAN SESAMA WARGA BINAAN DENGAN KESEJAHTERAAN SUBJEKTIF WARGA BINAAN LAPAS KLAS IIA PADANG - Hanifa Febrina; Rinaldi Rinaldi (Universitas Negeri Padang, 2020)
The study purpose to find threlationship between social support fellow the prisioners with subjective well-being the prisioners at Padang IIA Clas Prison. On this study use purposive sampling technique for the technique sampling with criteria is the inmates have non recidivist or the person who only once be the prisioner. 100 prisioners participated in this study. Data collection in this study use social support fellow the prisioners scale (reliability= 0,939), satisfactionwith life scale (reliability= 0,779), and positive affect negative affect schedule (reliability=0,809). Data tabulation in this study use product moment correlation technique from Karl Pearson. The result of hypotheses test are r=0,599, p=0,000 (p<0,05). This show that the significant of positive relation between social support fellow the prisioners with inmates subjective well-being at Padang IIA Clas PrisonTujuan penelitianadalah untuk melihat hubungan dukungan sosial teman sesama warga binaan dengan kesejahteraan subjektif warga binaan Lapas Klas IIA Padang. Dalam pengambilan sampel penelitian, digunakan teknik purposive sampling dengan kriteria warga binaan berstatus nonresidivis. Jumlah subjek penelitian sebanyak 100 orang warga binaan. Pengumpulandata menggunakan skala dukungan sosial teman sesama warga binaan (reliabilitas=0.939), skala satisfaction with life scale (reliabilitas=0,779), dan positive affect negative affect schedule (reliabilitas= 0,809). Data dianalisis menggunakan teknik korelasi product moment dari Karl Pearson. Hasil uji hipotesis adalah r:=0,599, p:0,000 (p<0,005). Hal ini menyatakan terdapat hubungan positif yang signifikan antara dukungansosial teman sesama warga binaan dengan kesejahteraan subjektif warga binaan Lapas Klas IIA Padang.